1996
DOI: 10.1109/75.544545
|View full text |Cite
|
Sign up to set email alerts
|

Frequency dependence of the constitutive parameters of causal perfectly matched anisotropic absorbers

Abstract: Perfectly matched layers (PML's), which are employed for mesh truncation in the finite-difference time-domain (FDTD) or in finite element methods (FEM's), can be realized by artificial anisotropic materials with properly chosen permittivity and permeability tensors. The tensor constitutive parameters must satisfy the Kramers-Kronig relationships, so that the law of causality holds. These relations are used to relate the real and imaginary parts of the constitutive parameters of the PML media to deduce the asym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
254
0
7

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 488 publications
(262 citation statements)
references
References 8 publications
1
254
0
7
Order By: Relevance
“…Other more involved functional dependencies of s x in terms of ω are also possible [15], but we do not consider those here. Assuming the absorber is located in the half-space x > 0, this is equivalent-from a transformation optics viewpoint-to a complexification of the spatial metric via [6] …”
Section: Metamaterials Blueprints For Reflectionless Absorbersmentioning
confidence: 99%
“…Other more involved functional dependencies of s x in terms of ω are also possible [15], but we do not consider those here. Assuming the absorber is located in the half-space x > 0, this is equivalent-from a transformation optics viewpoint-to a complexification of the spatial metric via [6] …”
Section: Metamaterials Blueprints For Reflectionless Absorbersmentioning
confidence: 99%
“…Festa and Vilotte [2005] have shown that, when B(x) = x, w c acts as a cut-off frequency, with an efficient absorption for w > w c . On the other hand, Kuzuoglu and Mittra [1996] proved in electromagnetics that causality is preserved when dB dx > 1, for any positive w c and dS dx . This result can be extended to elastodynamics, almost as far as the near-field P-S coupling can be neglected.…”
Section: Generalized Filtering Pml (Gfpml)mentioning
confidence: 99%
“…In the complex stretched coordinate approach (Chew & Weedon 1994;Kuzuoglu & Mittra 1996), the governing equation using CFS-PML can be rewritten as…”
Section: Implementation Of Cfs-pmlmentioning
confidence: 99%
“…The complex frequency stretched (CFS) PML, as introduced in Kuzuoglu & Mittra (1996), Roden & Gedney (2000) and Pan et al (2012), is one of a number of approaches that are suitable to mimic the reflection-free boundaries at the outermost surface of the interior domain. Table 1.…”
Section: Implementation Of Cfs-pmlmentioning
confidence: 99%
See 1 more Smart Citation